ANTIDEPRESSANT SCREENING OF LITHIUM CARBONATE IN THE PRESENCE OF PHENYTOIN USING A FORCED SWIMMING MAZE IN ALBINO MICE - aburawi, suhera; Saad, Shaban; ALgrabli, Amel (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2024)
Lithium was introduced into modern psychiatric medicine; in 1970, Lithium was approved by the Food and Drug Administration for the treatment of manic illness; later in 1974 is used for the prevention of manic-depressive illness. Aim of the study: To find out the effect of lithium on mental depression in the presence of phenytoin as a sodium channel blocker, using mice Methods: Male albino mice weighing between 25-40g are used. A forced swimming maze is used to screen for the effect of Lithium on mental depression. Drugs subacute administration is applied. Results: Lithium or phenytoin administration, each alone produces an antidepressant effect. While subacute administration of combined treatment of lithium and phenytoin produces an antidepressant effect less than the additive action of both lithium and phenytoin. Conclusion: Lithium has an antidepressant effect; also, phenytoin administration produces antidepressant action. Administration of phenytoin and lithium together, leads to a decrease in the pharmacological effect of each, as antidepressant, due to their interaction. Therefore, patients receiving the combined treatment of phenytoin and lithium should be under observation. Also, the free (unbound) phenytoin and lithium levels should be measured under medical control.